FINTECH IN IRAQ AND THE RISKS OF USING IT IN MONEY LAUNDERING OPERATIONS - Gailan Ismael Abdullah (Scholar Express Journals, 2022)
The research aims to identify the reality of Financial Technology (FinTech) in the Iraqi financial system, identify the developments that have affected it, and know the challenges and future prospects for them under the supervision of the Central Bank of Iraq, which supervises the work of FinTech companies and takes into account the developments in the financial and banking sector in light of global financial and banking innovations Many financial services have become dependent on FinTech for their implementation. Financial services are now provided outside of traditional financial institutions, which has contributed to improving financial access, increasing financial inclusion and thus increasing competition within the financial system, thus promoting economic growth. The use of FinTech –as an innovative means for granting credit and providing other financial services– involves many risks, perhaps the most important of which is the possibility of using FinTech in money laundering operations, which is one of the most important financial crimes affecting the financial system and then the economic system in general. Especially since FinTech has characteristics that make the process of transferring money through it more quickly and smoothly compared to traditional financial services, which would destabilize the economic system. Therefore, the research recommends the necessity of identifying and assessing money laundering risks related to financial products and services, as well as achieving financial integrity in light of FinTech and the systemic risks of cybercrime
Keywords: FinTech; Money; Banking Supervision; laundering